The use of multibeam backscatter angular response for marine sediment characterisation by comparison with shallow electromagnetic conductivity. (November 2016) - Monteys, Xavier; Hung, Peter; Scott, Gill; Garcia, Xavier; Evans, Rob L.; Kelleher, Brian
Abstract: In this empirically-driven research, multibeam backscatter angular response analysis is presented, together with shallow electromagnetic data and groundtruthing, to examine its suitability as a proxy for sediment characterisation. Backscatter angular curves extracted from Kongsberg EM1002 sonar (95–98 kHz), acquired in the Malin Basin to the northwest of Ireland, have been selected as a case study. Standard angular backscatter features and newly derived curvature features are examined and cross compared. Exhaustive statistical analysis has been performed on the data to elucidate the complex relationship between multibeam backscatter and sediment properties. Subtle subsurface sediment property gradients across the basin identified by the conductivity system are also captured by the newly derived backscatter features. The results reveal that Near-range backscatter is better suited for subsurface sediment characterisation in soft, fine-grained sediments than far-range. Furthermore, the analysis has constrained the optimum interval for such characterisation to in-between 4° and 16° for the parameters of this study. A number of shape features (slope, first derivative, second derivative and Fourier-smoothed least-squares-fitted curvature) have been examined, and their suitability discussed, in terms of sediment characterisation and, in particular, as potential proxies for delineating the boundary between sand- or silt-dominated sediment facies. Nonetheless, curvature features are found to be independent from average angular backscatter response, but outperform both first and second derivatives when correlating with conductivity in the central part of this case-study with fine-grained homogeneous sediments.